Effect of surface roughness on velocity fields through rock fractures - Sharifzadeh, Mostafa; Javadi, M.; Shahriar, K.; Mehrjooei, M. (n/a, 2009)
In many geological structures, the matrix permeability is negligible and the fractures are the main flow paths. The fluid flow and particle transport through rock fracture are increasingly important research topics mainly to the demands for design, operation and safety assessments of underground/surface constructions. In this paper, turbulent flow through an artificial three-dimensional rock fracture has been simulated by using finite volume method for a wide range of inlet velocities. The average velocity on several horizontal and vertical sections were calculated and normalized with inlet velocities. These normalized velocities have been used to illustrate roughness effect on flow velocity fields in rock fractures. The results show that; (i) by increasing flow rate, the symmetry of velocity profile decreases and incline to the smoothest fracture surface, also the intensity of rotational flow increases and, (ii) in high flow rates, the arrangement of flow channels changes and lower flow rates take place through large apertures.